Curing effect on the strength of cement mortar with bamboo biochar - Pragalanathan, Selvanathan; Pravina, K. Gunasekaran; Lai, Yeng Fock; Anand, N.; Chin, Siew Choo (Universiti Malaysia Perlis (UniMAP), 2024)
During the ongoing crisis, there is a growing apprehension regarding the escalating quantity of agricultural waste. As a result, it becomes imperative to explore alternative approaches for utilizing this surplus agricultural waste. Bamboo biochar is generated through the pyrolysis process, which involves subjecting it to high temperatures in an environment with limited oxygen. A recent study proposes the utilization of agricultural byproducts such as bamboo biochar as a partial substitute for cement in mortar. This research experiment involved incorporating varying percentages of bamboo biochar as a partial replacement for cement to assess the strength of cement mortar under different curing methods (water, air, and heat). The production of cement emits significant amounts of greenhouse gases, contributing to global environmental impact. The cement industry is recognized as the primary contributor to greenhouse gas emissions, accounting for approximately 6% of global warming. This study employs bamboo biochar as a partial replacement for cement in mortar to reduce cement usage in the construction industry. The study aims to determine the optimal water/cement ratio (0.40, 0.45, and 0.50) for enhanced flowability in mortar mixtures with a cement:sand ratio of 1:2.25. Additionally, it seeks to identify the optimal percentage of bamboo biochar in cement mortar to achieve optimal performance and determine the most effective curing method for cement mortar. The samples were subjected to curing for durations of 3 days, 7 days, and 28 days. Based on the obtained results, the optimal percentage for compressive strength was determined to be 2%, while for flexural strength, it was 0.5%. The water immersion curing method proved to be the most effective approach for curing mortar when partially replacing cement with bamboo biochar.